Correlation of Middle to Upper Eocene Units from High Latitude Southwestern Atlantic Sites - Rodriguez Amenabar, Cecilia; Guerstein, Gladys Raquel; Alperin, Marta Ines; Daners, Gloria; Casadio, Silvio Alberto; Rodriguez Raising, Martin Eduardo (Ameghiniana)
To understand the important significant climatic and paleoceanographic changes occurred in the Southern Hemisphere during the Paleogene, and especially those related to the opening of the Drake Passage, is essential to correlate the Eocene lithostratigraphic units in areas adjacent to this passage, such as those from the Austral-Magallanes and James Ross basins, to the north and to the south, respectively. For many years, there was no correlation between these units due to the absence of reliable chronostratigraphic and biostratigraphic information. Recently, other authors published U/Pb data for the Austral-Magallanes Basin and introduced important modifications to the previous stratigraphic scheme. Subsequently, due to reinterpretating the available isotope data together with U/Pb ages, the chronostratigraphic model has modified again, also including the James Ross Basin. In light of an updated quantitative dinoflagellate cyst dataset from the units adjacent to the Drake Passage, we performed a Principal Component Analysis (PCA) to discuss the correlation between the studied sections. The PCA groups assemblages with a high contribution of Antarctic taxa (e.g., Enneadocysta dictyostila, Deflandrea antarctica) containing in the Upper Member of the Río Turbio Formation (lower part), Man Aike, Leticia, and La Meseta formations, being Bartonian in age. The other group joined assemblages with younger ages, Priabonian, dominated by Antarctic species (Vozzhennikovia-Spinidinium) and cosmopolitan taxa, corresponding to the Upper Member of the Río Turbio Formation (upper part). This study reinforces the most recent chronostratigraphic proposal and proves the biostratigraphic useful of some taxa for sites near the Drake Passage. Fil: Rodriguez Amenabar, Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de ...